2020
DOI: 10.1186/s13006-020-00283-y
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of donor breastmilk banking among health workers: a cross-sectional survey in Zimbabwean urban settings

Abstract: Background The World Health Organization (WHO) recommends that donor human milk is superior to artificial infant formula in situations where the baby cannot feed on the mother’s breastmilk. The purpose of this study was to determine the acceptability of donor human milk banking among health workers in Zimbabwean urban settings. Methods A cross sectional study was conducted among 535 health workers and 15 key informants. Three referral hospitals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Similarly, a study conducted in SA reported that most healthcare professionals are more familiar with the breastmilk bank and that they understand the importance of donated breastmilk [ 23 ]. A study in Zimbabwe reported that healthcare professionals accepted the concept of human milk banking [ 19 ]. This may be because healthcare professionals understand the importance of breastmilk and breastmilk banks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, a study conducted in SA reported that most healthcare professionals are more familiar with the breastmilk bank and that they understand the importance of donated breastmilk [ 23 ]. A study in Zimbabwe reported that healthcare professionals accepted the concept of human milk banking [ 19 ]. This may be because healthcare professionals understand the importance of breastmilk and breastmilk banks.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in SA, KZN, supports the findings from the current study, where healthcare workers articulated certain cultural or religious beliefs that could have a huge influence on the acceptability of donated milk [ 25 ]. However, in a study conducted in Zimbabwe among healthcare workers, there were no religious issues associated with breastmilk donation [ 19 ]. Education is therefore needed to clear the misconceptions regarding breastmilk banking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, most of the subjects were female (62%) compared to the male (38%). A study on the acceptance of HMBs for health workers conducted in Zimbabwe showed that the majority of health workers were women, which was 72%, while for men it was 28% [11]. According to Sunaryo (2004), a person's behavior is influenced by several factors, one of which is genetic or endogenous factors, genetic factors originating from within the individual, including gender.…”
Section: Discussionmentioning
confidence: 99%